2017
DOI: 10.1177/0886260517708760
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Repeat Victimization and Sex Differences in South Korean Youth

Abstract: Interest in the correlates of victimization has significantly increased in criminology, while focusing on a few criminological theories, risky lifestyles/routine activities, and self-control. This study is to explore the applicability of five criminological theories, including social control theory, collective efficacy, and strain theories as well as risky lifestyles/routine activities and self-control to explain the correlates of repeat victimization. The current study also explores sex differences/similariti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 107 publications
1
2
0
Order By: Relevance
“…Regarding gender differences, results suggest that mean scores for girls were higher than for boys in perception of cohesion in school, but not in students' social control or teachers' social control. These results are consistent with other recent research (Barchia & Bussey, 2011;Cho, 2017;Lee & Jo, 2017), and thus provide validity to these scales. With regard to educational level differences, we found the mean scores for high school students to be higher than secondary students on perceptions of students' social control but not on cohesion or teachers' social control.…”
Section: Means Comparison (Hypothesis 3 Means Comparison)supporting
confidence: 93%
See 1 more Smart Citation
“…Regarding gender differences, results suggest that mean scores for girls were higher than for boys in perception of cohesion in school, but not in students' social control or teachers' social control. These results are consistent with other recent research (Barchia & Bussey, 2011;Cho, 2017;Lee & Jo, 2017), and thus provide validity to these scales. With regard to educational level differences, we found the mean scores for high school students to be higher than secondary students on perceptions of students' social control but not on cohesion or teachers' social control.…”
Section: Means Comparison (Hypothesis 3 Means Comparison)supporting
confidence: 93%
“…than boys throughout schooling (Barchia & Bussey, 2011;Cho, 2017;Lee & Jo, 2017). Nonetheless, research on school collective efficacy has produced limited evidence on age differences, with a single study found by the authors reporting that secondary students perceive a higher school collective efficacy than high school students (Barchia & Bussey, 2011).…”
Section: Article In Pressmentioning
confidence: 99%
“…A meta-analysis study has concluded that boys in adolescence were more likely to become bullying victims than girls [ 49 ]. Research on Korean adolescents also found that girls’ bullying victimization was highly correlated with deviant peer interaction than boys’ [ 50 ]. Although it could be inferred that gender may be a moderator between deviant peer affiliation and bullying victimization, there was still insufficient evidence to support the view on how it works.…”
Section: Introductionmentioning
confidence: 99%